Glutaraldehyde fixation method for single‐cell lipid analysis by time‐of‐flight secondary ion‐mass spectrometry. (10th April 2014) - Nagata, Yasuyuki; Ishizaki, Itsuko; Waki, Michihiko; Ide, Yoshimi; Hossen, Md Amir; Ohnishi, Kazunori; Sanada, Noriaki; Setou, Mitsutoshi; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; et al.
<x xml:space="preserve">Abstract</x> Lipid metabolism has attracted much attention in tumor biology studies. Recently, time‐of‐flight secondary ion‐mass spectrometry (TOF‐SIMS) imaging has enabled in situ lipid analysis of biological specimens with a submicrometer spatial resolution for analyses of tumor cells. In clinical settings, sample preservation is important, and specimens are often obtained from patients at different times; these samples must be preserved prior to measurement, and preservation techniques commonly involve chemical fixation with aldehydes. However, the influence of sample preservation on TOF‐SIMS analysis of fatty acids has not been reported. Thus, we examined the influence of glutaraldehyde fixation on TOF‐SIMS analyses by using the multiple myeloma cell line U266. We prepared two indium‐tin‐oxide‐coated glass slides on which cells were attached. One slide was fixed with 0.25% glutaraldehyde and rinsed in ammonium acetate buffer, whereas the other was left untreated. The specimens were subjected to TOF‐SIMS analyses in negative‐ion mode, and signals in the mass range of m/z 0–1850 were monitored. Both fixed and unfixed cells exhibited intense ion peaks corresponding to phosphoric acids and five types of fatty acids, putatively derived from membrane phospholipids. These ions were localized at the cell attachment site. We statistically compared the mean intensity of fatty acids between fixed and unfixed cells and found that both showed equivalent signals. Glutaraldehyde fixation was thus shown to be an effective method for preparing samples for single‐cell lipid analysis by TOF‐SIMS. Copyright © 2014 John Wiley & Sons, Ltd.